2022
DOI: 10.1111/febs.16592
|View full text |Cite
|
Sign up to set email alerts
|

C‐mannosylation regulates stabilization of RAMP1 protein and RAMP1‐mediated cell migration

Abstract: C-mannosylation is a unique type of protein glycosylation via C-C linkage between an a-mannose and a tryptophan residue. This modification has been identified in about 30 proteins and regulates several functions, such as protein secretion and intracellular localization, as well as protein stability. About half of C-mannosylated proteins are categorized as proteins containing thrombospondin type 1 repeat domain or type I cytokine receptors. To evaluate whether C-mannosylation broadly affects protein functions r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 45 publications
(65 reference statements)
0
3
0
Order By: Relevance
“…In some C ‐mannosylated proteins, C ‐mannosylation enhances protein stability [ 11 , 12 , 13 ]. CHX chase assay revealed that C ‐mannosylated RAMP1 is more stabilized than non‐ C ‐mannosylated RAMP1 [ 13 ]. Several reports have suggested that C ‐mannosylation affects protein conformations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In some C ‐mannosylated proteins, C ‐mannosylation enhances protein stability [ 11 , 12 , 13 ]. CHX chase assay revealed that C ‐mannosylated RAMP1 is more stabilized than non‐ C ‐mannosylated RAMP1 [ 13 ]. Several reports have suggested that C ‐mannosylation affects protein conformations.…”
Section: Discussionmentioning
confidence: 99%
“…In some C-mannosylated proteins, C-mannosylation enhances protein stability [11][12][13]. CHX chase assay revealed that Cmannosylated RAMP1 is more stabilized than non-Cmannosylated RAMP1 [13]. Several reports have suggested that C-mannosylation affects protein conformations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation